National German Guideline (S2k): Guideline for the Diagnosis and Treatment of Endometriosis - Ulrich, U.; Buchweitz, O.; Greb, R.; Keckstein, J.; von Leffern, I.; Oppelt, P.; Renner, S. P.; Sillem, M.; Stummvoll, W.; De Wilde, R.-L.; Schweppe, K.-W.; for the German and Austrian Societies for Obstetrics and Gynecology (Geburtshilfe und Frauenheilkunde, 2014)
In this guideline, recommendations and standards for optimum diagnosis and treatment of endometriosis are presented. They are based on the analysis of the available scientific evidence as published in prospective randomized and retrospective studies as well as in systematic reviews. The guideline working group consisted of experts from Austria, Germany, Switzerland, and the Czech Republic.
Keywords: endometriosis; laparoscopy; reproductive medicine; health care